The Harlem Renaissance and its role in resisting racial discrimination against African Americans - Mohammed, Assist.Lect. Falah Khalaf (Thi Qar Arts Journal, 2022)
During the early 1900s, Harlem experienced a cultural renaissance that changed the course of its history. This period started in the twenties and lasted until the mid-30s. During the period of time known as the New Negro, African American culture grew much more than just socially during the Harlem Renaissance. The movement sparked new literary and artistic works as well as trends in fashion and music. Some of these trends even changed the way people thought about their race; they became more prideful and intellectual. People living in Harlem came together to create a new sense of cultural pride and racial identity. African-Americans changed the public perception of them by breaking the traditional style. As a result, many people identify themselves as black generations after this event.